Edukasi Pentingnya Akses Sanitasi Jamban yang Layak untuk Meningkatkan Kesadaran Masyarakat Kabupaten Kendal melalui Iklan Layanan Masyarakat - Rayhan Yoga Pratama; Abi Senoprabowo (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
This study examines the importance of educating the community about access to proper sanitation facilities, especially toilets, in Kendal Regency. This study explores the effectiveness of public service advertisements (PSAs), especially posters, in raising awareness about sanitation. Using a qualitative research approach, this study combines data collection methods such as interviews, observations, and literature studies to design this PSA campaign. The analysis was conducted using Robin Landa's design process approach with the stages of orientation, analysis, concept, design, and implementation. This study emphasizes the importance of an educational approach that is tailored to local social and cultural conditions to address sanitation problems. The findings of the study indicate that public service advertisements through posters are an effective tool for changing community behavior and creating a healthier environment by promoting good sanitation habits. This study concludes that continued efforts are needed to strengthen the reach and impact of sanitation awareness campaigns, by involving relevant parties, such as local governments, health facilities, and community leaders, to ensure widespread adoption of better sanitation practices. This study contributes to efforts to improve sanitation in rural areas by proposing practical solutions for effective public education campaigns.